Pendapat Pimpinan-pimpinan Gereja di Bekasi tentang Izin Pendirian Rumah Ibadah dalam Peraturan Bersama Menteri Tahun 2006 - Binsar Antoni Hutabarat (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT:The article, entitled "Opinion The church Leaders in Bekasi on the Permit Construction of Houses of Worship in the Joint Regulation of the Minister of the Year 2006, will be explained about the implementation of policies permit the establishment of houses of worship in Joint Regulation of the Minister (PBM) in 2006 in Bekasi, as well as the implications for church in that place, through the opinion of the church leaders in Bekasi. First, authors will describe the Guarantee Rights of Religion, Belief, Worship and Establish Home Worship based on Pancasila and the Indonesian Constitution, the Universal Declaration of Human Rights, The Covenant, and documents declarations of the United Nations (UN), and also explained about permit the establishment of houses of worship of Letters Joint Decree (SKB) until the PBM. After that, will be presented regarding the results of the opinion of the church leaders in Bekasi on the implementation of the policy permits a house of worship in Bekasi. Opinion leaders in Bekasi Church will be grouped in four categories, namely: A) The church which has a license, and not problematic. B) The church is having problems obtaining a license, a problem with the public, but finish. C) The church that does not have a license but has no problem with the community. D) The church that does not have permissions and have problem with the community, and did not finish. The findings obtained are church leaders in the four categories above found PBM on authorizing the establishment of houses of worship contrary to Pancasila and the Indonesian Constitution and the values of human rights are universal, and implementation of government policies that adversely affect the lives of religious believers in Bekasi, both in the internal relations of religion, as well as in interreligious relations.Â KEYWORDS: permit the establishment of houses of worship, Joint Ministerial Decree, Pancasila, the Indonesian constitution, human rights